Relações entre mídia e lazer:o capitalismo, os meios e a apropriação do tempo livre nas sociedades industrial e pós-industrial - Raulino, Gabriela Dalila Bezerra (2013)
This research aims to understand the relationship between media, capitalism and ownership of free time for leisure practices in industrial societies and postindustrial. Searching is thus a conceptual framework that takes into account the kind of ideology that naturalizes the relationship of leisure with the foundations of contemporary media, and the media only with leisure, forgetting their insertion in the labor and industrial relations in society. We intend to demonstrate that every mode of production, in the capitalist system, entails a mode of reproduction. Methodologically, this is a first approximation, from theoretical concerns already performed, constituting a theoretical research, bibliographic and descriptive character. The results of the text drives us to the conclusion that the work and leisure spheres tend to be less and less differentiated, since both remain as activities of product management with the same intellective protocols, based on information and communication technology, and that accordingly, the media favors an expansion of productive activity even during leisure time